Combinations of trabecular and cortical bone properties distinguish various loading modalities between athletes and controls. Issue 3 (27th November 2020) - Saers, Jaap P. P.; DeMars, Lily J.; Stephens, Nicholas B.; Jashashvili, Tea; Carlson, Kristian J.; Gordon, Adam D.; Shaw, Colin N.; Ryan, Timothy M.; Stock, Jay T.
Abstract: Objectives: Variation in trabecular and cortical bone properties is often used to infer habitual behavior in the past. However, the structures of both types of bone are rarely considered together and may even contradict each other in functional interpretations. We examine trabecular and cortical bone properties in various athletes and sedentary controls to clarify the associations between combinations of cortical and trabecular bone properties and various loading modalities. Materials and methods: We compare trabecular and cortical bone properties using peripheral quantitative computed tomography scans of the tibia between groups of 83 male athletes (running, hockey, swimming, cricket) and sedentary controls using Bayesian multilevel models. We quantify midshaft cortical bone rigidity and area (J, CA), midshaft shape index (Imax/Imin), and mean trabecular bone mineral density (BMD) in the distal tibia. Results: All groups show unique combinations of biomechanical properties. Cortical bone rigidity is high in sports that involve impact loading (cricket, running, hockey) and low in nonimpact loaded swimmers and controls. Runners have more anteroposteriorly elliptical midshafts compared to other groups. Interestingly, all athletes have greater trabecular BMD compared to controls, but do not differ credibly among each other. Discussion: Results suggest that cortical midshaft hypertrophy is associated with impact loading while trabecular BMD is positively associated with both impact and nonimpact loading. Midshaft shape is associated with directionality of loading. Individuals from the different categories overlap substantially, but group means differ credibly, suggesting that nuanced group‐level inferences of habitual behavior are possible when combinations of trabecular and cortical bone are analyzed.